A comparative study of corporate social responsibility in English and German professional football - Jäger, Johannes; Fifka, Matthias (Soccer and Society, 2020)
We build on institutional theory to study Corporate Social Responsibility (CSR) practices in English and German football clubs. We examine how the countries' political, legal, economic, social, and cultural frameworks impact their CSR approaches and to what degree they allow for a transfer of CSR instruments and activities. Our results, based on 24 expert interviews, show that English club representatives focus on community issues, while their German counterparts take a more holistic approach. Moreover, the organizational integration of CSR differs, as English clubs rely on financially independent charities, while German clubs carry out most of the activities themselves. While financial resources also differ, clubs in both countries employ similar non-monetary resources for their initiatives. Our findings serve as a foundation for further studies amongst a wider geographic range of European football clubs and demonstrate that institutional theory serves well as a framework for comparative studies on CSR in football.
CRIS-Team WoS Importer:2020-05-02